Measurement of Pamong Performance in Agency Early Childhood Education Development and Community Education - Rahmat, Abdul; Badu, Syamsu Qamar (Universitas Negeri Semarang, 2018)
Work productivity is the ability associated with the mental attitude of a pamong in making improvements and self-improvement in carrying out its professional duties so as to realize the hope and desire of the nation to achieve the better quality of education. The objective to be achieved by doing this research is to see the productivity measurement of pamong work and to know which variable the most dominant influence on the productivity of pamong work is. This research was conducted at Agency Early Childhood Education Development and Community Education Gorontalo 2018. To collect data in this research, field research method is used, that is research done directly to the research object. The techniques used are interviews, documentation, and questionnaires. The population in this study is the civil servant, technically the writer cannot examine each tutor or individual. Where the sampling method is done by using a random sampling technique. To obtain the data needed in this study used questionnaire survey techniques. From result of regression analysis showed that work productivity is influenced by five motivation motivation, physiological requirement (X1) = 0.699, need for safety (X2) = 0.720, social needs (X3) = 0.706, need for achievement (X4) = 0.677, self-actualization needs (X5) = 0.542. While the most dominant variable affecting the productivity of the civil service is the need for a sense of security of 0.720. There is an influence of motivation and partially significant effect seen from the fifth attribute, that is a physiological requirement for count equal to (2,540), need for security for count (3,869), social requirement for count (3,163), need for achievement the value of t count is (2.294), the need for self-actualization for the value of t count is (3.127). and together influence work productivity is seen from the value of table as much as (54,490).